Genetic drivers for resistance and susceptibility traits in Atlantic salmon (Salmo salar) towards salmon lice (Lepeophtheirus salmonis) - James Abraham, Jeff (UiT The Arctic University of Norway, 2021)
Salmon lice (Lepeophtheirus salmonis), a common parasite on salmonids is one of the biggest problem the aquaculture industry faces today. The current methods used to combat salmon lice in farmed Atlantic salmon (Salmo salar) industry are often considered to affect the ecosystem negatively; and inefficient in a long run long run due to development of resistance in the parasite. The potential of methods involving epigenetic modification of farmed fish to develop a lice resistant progeny of farmed salmon is not widely explored. A systematic literature review was used to collect and analyse data from peer reviewed scientific articles, science journals and industrial reports. Data were extracted from 55 peer reviewed articles, 2 science journals and 3 industrial reports based on the inclusion criteria. The summary results lice resistance in Atlantic salmon is described to be a polygenic trait. The differential expression of immune related genes have a significant role in variation in resistance and susceptibility of Atlantic salmon towards salmon lice. Vaccines and immune-modulatory in-feed additives could induce differential gene expressions leading to increased lice resistance in salmon. The heritability of lice resistance trait in salmon is moderate to low, but could be improved with epigenetic methods including selective breeding. The epigenetic memory in salmon is reported to be preserved in the form of DNA methylation. Taking this into account, the epigenetic memories of previous lice infection and differential gene expression could be stored fish DNA and potentially inheritable. Further research on epigenetic memory in Atlantic salmon on the perspective of the trait for lice resistance would be a great step towards developing a lice resistant progeny of salmon. However, the impacts of epigenetic modification on farmed salmon and ecosystem have to be considered in further studies.